Employees balance and stability as key points in organizational performance. (5th March 2021) - Neves, José; Maia, Nuno; Marreiros, Goreti; Neves, Mariana; Fernandes, Ana; Ribeiro, Jorge; Araújo, Isabel; Araújo, Nuno; Ávidos, Liliana; Ferraz, Filipa; Capita, António; Lori, Nicolás; et al.
Abstract: System analyses deal with interrelationships between different variables that keep the system in balance. In many analysis of complex thinking, a system is viewed as a complex unit in which the 'whole' is not reduced to the 'sum' of its parts; the system becomes an ambiguous item because it consists of several entities that interact with unforeseen results or, in other words, it is situated at a transdisciplinary level, it is impossible for an area to have a complete reading of its complexity. It was also mentioned that the concept of the open system best describes complexity by stating that 'the laws of the organization are not equilibrium, but an imbalance that is restored or compensated for by stabilized dynamics'. This idea originated from the field of thermodynamics and the second law, in which the imbalance that it maintains allows the system for an apparent balance. This fragile steady state has something of a paradox, since the structures remain the same, but their constituents are changeable. The concept of open system undoes the door to a theory of evolution that can only derive from the interactions between a system and its ecosystem. Within this systemic approach, the focus of the analysis takes into account the ambiguity, multidisciplinary and complexity associated with system adjustment, i.e. it is intended to qualify an employee job based on their experience and knowledge as a measure of their impact on the organization performance.